An antibiotic susceptibility testing trial organised as part of the United Kingdom national external microbiological quality assessment scheme. Issue 11 (November 1982) - Snell, J J; Brown, D F; Gardner, P S
Abstract : Organisms of known susceptibility to antimicrobial drugs were distributed for sensitivity testing to laboratories participating in the United Kingdom National External Microbiological Quality Assessment Scheme. The results obtained were correlated with the methods used. Laboratories differed in their standards of antimicrobial drug sensitivity testing. An association between error rates and particular methods and practices enabled recommendations to be made on disc content, method of methicillin testing, preparation of inoculum, use of controls and use of lysed blood for sulphonamide testing. Some media appeared significantly better than others but because of the many factors involved further information is being sought to clarify this.